2009
DOI: 10.3189/002214309790794887
|View full text |Cite
|
Sign up to set email alerts
|

Terminus dynamics at an advancing glacier: Taku Glacier, Alaska

Abstract: ABSTRACT. Taku Glacier, Alaska, USA, is currently in the advance stage of the tidewater glacier cycle. We investigated the near-terminus dynamics by measuring surface velocities, surface elevation changes, ice thickness and ablation. Velocities vary on sub-daily, diurnal, seasonal and interannual timescales. Flowline modeling shows that the modeled surface velocities are sensitive to changes in till yield strength and thus effective basal pressures. The glacier bed deepens in the up-glacier direction and this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 28 publications
6
35
0
Order By: Relevance
“…1 for glacier locations). Margerie, Johns Hopkins, and Taku Glacier are some of the few currently advancing tidewater glaciers in Alaska (e.g., Motyka and Echelmeyer, 2003;Truffer et al, 2009;McNabb and Hock, 2014), while Rendu Glacier has been previously identified as a surge-type glacier (Field, 1969). The pattern of elevation change shown on Rendu Glacier in Fig.…”
Section: Uncertaintiesmentioning
confidence: 92%
“…1 for glacier locations). Margerie, Johns Hopkins, and Taku Glacier are some of the few currently advancing tidewater glaciers in Alaska (e.g., Motyka and Echelmeyer, 2003;Truffer et al, 2009;McNabb and Hock, 2014), while Rendu Glacier has been previously identified as a surge-type glacier (Field, 1969). The pattern of elevation change shown on Rendu Glacier in Fig.…”
Section: Uncertaintiesmentioning
confidence: 92%
“…As a result of global warming, the number of glaciers in Greenland that currently have floating termini has rapidly diminished; most are now grounded [ Enderlin and Howat , ]. In Alaska, surface ablation rates at tidewater glaciers can exceed 10 m yr −1 [e.g., Truffer et al , ] and these coastal glaciers receive significant liquid precipitation at lower elevations during the warm season. Both meltwater and rain ultimately exit the glacier as subglacial discharge (Figure ).…”
Section: Morphologies Of Glacier Termini In Various Settingsmentioning
confidence: 99%
“…This is in part because the only "marine-terminating" glacier on the Juneau Icefield, Taku, has developed a terminal moraine through excavation of proglacial sediments that prevents it from calving (e.g., Criscitiello et al, 2010). The lack of calving and high AAR (Accumulation Area Ratio-the fraction of the glacier that is in the accumulation zone) of Taku Glacier both contribute to mass gain and advance there (e.g., Larsen et al, 2007;Pelto et al, 2008;Truffer et al, 2009;Criscitiello et al, 2010;Melkonian et al, 2014;Larsen et al, 2015). Thus, Taku is another example of a marine-terminating glacier that has a disproportionately large effect on the total mass balance an icefield, just like the four large outlet glaciers at Stikine.…”
Section: Thinning At Marine Vs Land-terminating Glaciersmentioning
confidence: 99%